CIVIL INHERITANCE CASES IN COURT HEARINGS ACCORDING TO JUDICAL PROCEDURE AND ISSUES OF JURISDICTION (World Bulletin of Management and Law, 2023)
Civil cases involving inheritance issues are, by their nature, complex matters. In civil procedural law, civil cases are not divided into categories of simple and complex cases. However, the court (judge), when considering the content of the case, must determine the size of the claims, the substantive law that should be applied, the circle of interested parties who should be involved in the case, and the issues to be resolved during the case hearings. The number of plaintiffs and defendants, determining the circumstances relevant to the case, appointing an expert, and taking into account other circumstances—some cases in judicial practice are considered complex.
Keywords: Civil cases; civil procedural law